IMPLEMENTASI GEOGEBRA DALAM MATERI GRAFIK FUNGSI LINIER PADA SISWA SMP NEGERI 30 MALUKU TENGAH - Salamor, Reinhard; Kempa, Vicardy; Rumalean, M Samad (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
Digital transformation has brought about major changes in the world of education. Many applications have been created to facilitate learning in the classroom. GeoGebra is one such application that has been developed with simpler features so that students can apply it effectively. Community service activities are an important moment for universities to disseminate their research results. The Mathematics Education Study Program also takes part in efforts to improve the quality of education in Maluku through community service programs (PkM) based on research conducted by lecturers and collaborations between lecturers and students, particularly those related to the use of GeoGebra. This activity is necessary because mathematics is abstract in nature, making it difficult for many students to understand the material well. This condition was also found during the initial observation by the community service team at SMP Negeri 30 Maluku Tengah. Therefore, mathematics education lecturers and students conducted community service (PkM) at SMP Negeri 30 Maluku Tengah with a seminar and training approach, one of which was about the use of GeoGebra in linear function graph material. The students' responses showed that (1) Students felt that GeoGebra helped them solve math problems (mean of 4.04 with a good rating); (2) The development of GeoGebra software was easier to apply so that students could use it well (mean of 3.92 with good criteria); and (3) Students were more enthusiastic about learning mathematics and wanted better grades from their mathematics learning (mean of 3.93 with good criteria).